PRAGMATIC AND RHETORICAL STRATEGIES IN THE ENGLISH-WRITTEN JOKES - Rochmawati, Dyah (Indonesian Journal of Applied Linguistics, 2017)
Understanding verbal jokes in English is problematic for English as Foreign Language (EFL) readers since understanding the jokes requires understanding their linguistic, cultural and social elements. Since a joke constitutes a complex and paradoxical phenomenon, it needs multiple approaches of analyses—such as pragmatic and rhetorical analyses—in order to investigate the multiple layers of meanings it carries. Recently there has been a shift in humor studies, emphasizing linguistic humors and involving the field of rhetoric. These studies, however, have mostly addressed the connection between rhetoric and spoken jokes in persuasion. The present study therefore applied Austin’s Speech Act Theory (1975) and Grice’s Cooperative Principles (1957), and Berger’s rhetorical techniques (1993) to crack the funniness of the written jokes. Specifically, the study aims at describing: how the (1) rhetorical and (2) pragmatic strategies are used in the jokes, and (3) how the pragmatic and rhetorical strategies complement to create humor. The study employed a qualitative research method. Some jokes were purposively selected from the Reader’s Digest and two online sources: http://jokes.cc.com/, and http://www.ajokeaday.com/. Document studies were the means of data collection. The collected data were then analyzed using a qualitative content analysis. The results showed that that there was a relationship between the two pragmatic theories, i.e., Speech Act Theory and Cooperative Principles, and Berger’s rhetorical techniques. The results offered an alternative reading and richer understanding of how written jokes employed pragmatic and rhetorical strategies to advance their rhetorical objectives and humor functions.